Exploring fungi associated with the perennial grain crop intermediate wheatgrass - Dahal, Anusha (Kansas State University, 2023)
Perennial crops, such as intermediate wheatgrass (IWG), have been recognized as a valuable component of sustainable agriculture, providing ecosystem benefits while minimizing adverse effects of conventional farming on the environment. Domestication of intermediate wheatgrass as a grain crop began in 1980s, and grain harvested from it is marketed as Kernza®. As adoption of this crop increases, farmers have expressed concerns about potential disease and pest issues and mycotoxin contamination of the grain. Though IWG has been used extensively as a donor of disease resistance genes to annual crops like wheat, there may still be diseases that cause detrimental effects to food and feed. To address these concerns, this study aims to characterize the fungal and viral populations from the grain samples. Head samples were collected from farmers in Kansas, Minnesota, North Dakota and Montana, and leaf samples were obtained from an IWG nursery in Olathe, Kansas. The head samples were sterilized, cultured, single-spored, and DNA was extracted. Polymerase chain reaction (PCR) was performed using ITS and Tef-1[alpha] primers and then sequenced. The results from the head samples confirmed the presence of diverse Fusarium species such as, Fusarium graminearum, Fusarium incarnatum-equiseti species complex, Fusarium armeniacum, Fusarium verticillioides, Fusarium asiaticum, Fusarium boothii, Fusarium sporotrichioides, and Fusarium lacertarum. The analysis of mycotoxins in representative grain samples revealed presence of regulated mycotoxins including DON, fumonisin, zearalenone, and T-2. DNA sequencing of leaf samples showed the presence of important leaf disease causing fungal pathogens including Pyrenophora tritici-repentis which causes tan spot, Bipolaris sorokiniana which causes spot blotch, and Parastagnospora nodorum which causes leaf blotch. The nanopore sequencing of leaf samples revealed the presence of wheat streak mosaic virus, soil borne wheat mosaic virus, and barley yellow dwarf virus. The information gathered from this study is valuable for farmers and researchers who seek to understand disease diversity in domesticated IWG and develop effective breeding and disease management strategies. While the presence of some disease-causing pathogens has been confirmed in IWG, further research is needed to understand other pathogens, host-pathogen interactions, and their localization in the crop to obtain a comprehensive knowledge of crop pathology.
Keywords: Intermediate wheatgrass; Kernza; Head diseases; Fusarium spp.; Fusarium head blight; Mycotoxin